Representasi Mitos dalam Film Dokumenter - Apip Apip (LP2M ISBI Bandung, 2011)
ABSTRACTThis research studies the representation form of myth in Ray Bachtiar Drajat’s film, “Ngalaksa” (2004). This research is using qualitative method to understand the representation form of myth in documentary film. The data analysis uses the methodof Charles Sanders Peirce’s semiotics. This research shows that, Ray Bachtiar sees ngalaksa ritual which is full symbol and ritual offerings as concrete examples of collage, montage, and assembling concepts which have been embraced by in the field of photography. This reality inspires Ray to actualize representation of ngalaksa in the form of documentary film when photography and multimedia arts are not satisfying enough for his expression, especially, for revealing facts into a discourse narratively. The dissolve of drawing, photo, video, and audio smoothen the representation of ngalaksa ritual which is closed to the thought background of myth, cosmology and agricultural life.Key words: ngalaksa, documentary film, representation of myth